Phylogenetic Analysis of the Nucleoprotein Gene of Newcastle Disease Vaccine Viruses in India - Pushpa, R.N. Ramani; Kirubaharan, J. John; Koteeswaran, A. (International Journal of Poultry Science, 2009)
The Nucleoprotein (NP) gene of four different vaccine viruses of NDV commonly used in India namely D58, LaSota, F and K were characterized to find out variations if any. The NP gene was observed to have 1747 nucleotides with a coding sequence of 1470 nucleotides coding for 489 amino acids in all four vaccine viruses irrespective of their virulence to chickens. The variations at the coding sequence were restricted mostly to positions 401-489 and positions between 1 and 400, irrespective of pathogenicity to chickens remain conserved. The epitopes in nucleoprotein gene was also predicted. Among the 20 different epitopes predicted in the NP gene, one epitope with sequence 447FLDLMRA453 was found conserved in all vaccine viruses and was also found to be immunodominant.